2020
DOI: 10.1001/jamainternmed.2019.7143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Payment Changes and Choosing Wisely Recommendations for Use of Low-Value Laboratory Tests in the United States and Canada

Abstract: IMPORTANCE Evidence comparing the consequences of Choosing Wisely recommendations across health systems or with the consequences of recommendations plus policy change is lacking.OBJECTIVES To compare changes in the use of 2 low-value laboratory tests after the release of Choosing Wisely recommendations across 3 health care jurisdictions and changes associated with a related policy change. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study was a population-based interrupted time series of adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 28 publications
(53 reference statements)
0
67
0
Order By: Relevance
“…Some authors, as a consequence, believe that prescribing or paying restrictions (self-pay for high dose) should be put in place by authorities. 21,45 We suggest that a standardized operationalization of PIPPI, as presented in this study, offers opportunities to measure PIPPI use more validly, to compare its occurrence across health service providers, settings, and care models, and possibly to incentivize a more cautious use of PPI drugs, while increasing transparency and awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors, as a consequence, believe that prescribing or paying restrictions (self-pay for high dose) should be put in place by authorities. 21,45 We suggest that a standardized operationalization of PIPPI, as presented in this study, offers opportunities to measure PIPPI use more validly, to compare its occurrence across health service providers, settings, and care models, and possibly to incentivize a more cautious use of PPI drugs, while increasing transparency and awareness.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 57 , 58 On the demand side, encouraging use of shared decision-making and aligning benefit design with payment reform could also be associated with incremental success, particularly when carefully targeting cost sharing exclusively toward low-value care. 59 , 60 , 61 , 62 To be sure, financial incentives are necessary but likely insufficient by themselves, 1 , 8 , 63 , 64 considering that a 2017 systematic review 47 of interventions to reduce low-value care found that multicomponent interventions are associated with superior outcomes compared with single-component interventions. Most likely, a combination of capitated payment models combined with physician engagement and culture change, alongside the implementation of seamless EHR CDS tools, may have the greatest chance of success in eliminating low-value care.…”
Section: Discussionmentioning
confidence: 99%
“…While expanding and strengthening capitated and ACO payment models may be associated with larger changes in physician behavior, policy makers must also carefully monitor for unintended harms, such as decreases in use of high-value care 1,2,57,58. On the demand side, encouraging use of shared decision-making and aligning benefit design with payment reform could also be associated with incremental success, particularly when carefully targeting cost sharing exclusively toward low-value care [59][60][61][62]. To be sure, financial incentives are necessary but likely insufficient by themselves,1,8,63,64 considering that a 2017 systematic review47 of interventions to reduce low-value care found that multicomponent interventions are associated with superior outcomes compared with single-component interventions.…”
mentioning
confidence: 99%
“…Similar factors may also play a role in other non-US health systems, such as Canada’s, where low-value care is broadly present despite operating largely within a single payer system. 30 Identifying these factors will be essential for the development of interventions to reduce the delivery of such care in the VHA and other integrated health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…To aid in this task, our claims-based approach to identify low-value testing may help the development of future value-based metrics. 23 , 30 , 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%